Rates of Nicosulfuron Applied in Glyphosate-Tolerant and Sulfonylurea-Tolerant Soybean - SILVA,A.F.M. (2019)
ABSTRACT: STS cultivars tolerate up to four times higher rates of chlorimuron than those recommended for non-tolerant cultivars, without significant damage. However, few studies position the selectivity of nicosulfuron in STS cultivars. The aim of this study was to assess the selectivity of rates of the herbicide nicosulfuron applied in the post-emergence (V4) of RR/STS soybean. The experiments were conducted in the 2015/16 and 2016/17 seasons in Piracicaba, SP. In the 2016/17 season, the experiment was also conducted in Palotina, PR. Treatments consisted of six rates of the herbicide nicosulfuron (0, 50, 100, 150, 200, and 250 g a.i. ha-1). The experimental design was a randomized block design with four replications. The symptoms of injury were assessed at 7, 14, 21, and 28 days after application, as well as the assessment of variables related to the agronomic performance (plant height, number of pods per plant, yield, and one thousand-grain weight). The data were submitted to regression analysis (p<0.05). The estimated rates reduced yield by 5% in relation to the rate 0 and were between 57.79 and 68.37 g a.i. ha-1. In general, the RR/STS soybean is tolerant to the application of nicosulfuron up to 57.79 g a.i. ha-1 when considering the estimated rates. Therefore, the RR/STS soybean is tolerant to the application of nicosulfuron up to 50 g a.i. ha-1, according to the applied rates.